217k views
1 vote
Solve system of equation by substitution

Solve system of equation by substitution-example-1
User Ktr
by
5.0k points

2 Answers

7 votes

Answer:

y=2 and x=0

Explanation:

If you plug in x=-y+2 into the equation of

3y+(-y+2)=6 now combine like terms and solve for y

plug y into the x=-y+2 and then solve

User Penner
by
5.0k points
5 votes

Answer:

y= 2

x= 0

Explanation:

okay your going to substitute -y+2 for x in the other equation

so it be 3y+(-y+2)=6

combined like terms and get 2y+2 = 6

subtract 2 by both sides and divide 2 from both to get y= 2

now plug y= 2 into the first equation to get x

x = -2 +2

User Ravioli
by
5.0k points